A novel crease-resistant and hydrophobic dual-function foam coating for silk fabric by the one-step method. Issue 13 (July 2020) - Ge, Fangqing; Zhang, Jinju; Liu, Jingyan; Fei, Liang; Wang, Chaoxia
A dual-function silk fabric possessing crease-resistance and hydrophobicity is obtained by one-step foam finishing. A system with a high foaming ratio, containing hydrophobic reagent, crease-resistant agent, and foaming agent, is achieved by optimizing the hydrophobic agent. The results show the foamability and foam stability of finishing solution are enhanced slightly with the increase of the foaming agent dosage. The hydrophobicity and crease-resistance of the treated silk fabric are significantly improved. The contact angle of the treated silk fabric is increased to 132.6 ± 0.7° with the hydrophobic agent addition; meanwhile, the crease recovery angle was improved from 212.5 to 230.3° compared with the silk treated by crease-resistant agent, resulting from the cross-linking reaction of hydroxyls between the hydrophobic agent and silk fabric. SEM images reveal that the surface roughness of the finished silk fabric exhibits an obvious enhancement, indicating a film is formed by the resin curing on the fabric surface, which also explains why the crease-resistance and hydrophobicity of silk fabric are improved. The tearing strength retention ratio is increased 160% after the one-bath finishing of crease-resistant reagent and hydrophobic agent, and the breaking strength of the silk fabric is well maintained. The one-step foam finishing is a facile and energy-saving technology to endow the silk fabric with crease-resistance and hydrophobicity dual-function.